Coupled thermo–mechanical interface model for concrete failure analysis under high temperature - Caggiano, Antonio (2015)
A thermo–mechanical interface model for failure analysis of concrete subjected to high temperature is presented in this work. The model is an extension of a fracture energy-based interface formulation which now includes thermal damage induced by high temperature and/or fire. The coupled thermal–mechanical effect in the interface model is taken into account through the formulation of a temperature dependent maximum strength criterion and fracture energy-based softening or post-cracking rule. In this sense, the strong variation of concrete ductility during failure processes in mode I, II or mixed types of fracture is described through the consideration of temperature dependent ductility measures and of the specific work spent in softening. Moreover, a temperature-based scaling function is introduced to more accurately predict the thermal effect affecting the interface strength and post-cracking response. After outlining the mathematical formulation of the interface model, numerical analyses are presented to validate its soundness and capability. A wide range of experimental results, available in the scientific literature, are analyzed at both material and structural scale of analysis using the proposed interface model and in the framework of the discrete crack approach. The results demonstrate the predictive capabilities of the proposed interface constitutive theory for temperature dependent failure behavior of concrete.